COVID 19 koşullarında sağlık çevirmenliği hizmetleri ve toplum_x000D_ _x000D_ çevirmenliğinde “Yeni Normal”’i düşünmek_x000D_ - (:unkn) unknown (My University, 2020)
Dünyayı etkisi altına alan COVID-19'un ülkemizdeki ilk vakaları 2020 Mart ayı başında görülmüştür. Hastalığın yayılması hem dünyada hem de Türkiye’de diğer alanlarla birlikte iş dünyasını da büyük ölçüde etkilemiş ve bu durumun çeviri sektörü ve çevirmenlik hizmetlerine çeşitli yansımaları olmuştur. Bu bağlamda, içinde bulunulan sürecin sosyal, ekonomik, ticari vb. tüm alanlarda yeniden düşünme, gözden geçirme ve hatta köklü değişiklikler yapma gerekliliğini ortaya çıkaracak nitelikte olduğu düşünülebilir. Hiç kuşkusuz, sağlık sektörü bu dönemde en çok etkilenen alanların başında gelirken, sağlık çevirmenliği hizmetlerinin COVID-19 koşullarında nasıl verildiği sorusu da araştırılmaya muhtaç bir konu olarak belirginleşmiştir. Bu ihtiyaçtan hareketle pandemi süreci özelinde sağlık kuruluşlarına başvuran hastalara ve sağlık personeline çevirmenlik yapan kişilerin durumunu ve çalışma koşullarını ortaya koymayı amaçlayan bir anket uygulanmıştır. Anketten elde edilen veriler, Toplum Çevirmenliğinin “yeni normal”i açısından irdelenmiş ve meslekleşme/profesyonellik sürecine etkileri bakımından değerlendirilmiştir.

Having influenced the world from the end of 2019, COVID-19 manifested itself with its first cases at the beginning of this year in our country as well. Industries both across the world and in Turkey have been greatly affected by the spread of the disease. This, in turn, has had several effects, both positive and negative, on translation/interpreting sector and services, as well as many other sectors. In the meantime, the concept "new normal" has emerged as a paradigm forcing us to rethink fundamentally in all areas within the social, economic, and commercial framework. Undoubtedly, since the healthcare sector is one of the most affected areas during this pandemic, the question of how healthcare interpreting and translation services are provided under COVID-19 conditions arises as a topic requiring research. Based on this need, a survey was applied to reveal the situation and working conditions of the healthcare interpreters and translators who translate for the health professionals and patients in healthcare institutions, with a focus on the pandemic process. The present study examines the findings of this survey, which was carried out specifically for healthcare interpreters and translators, in terms of the “new normal” concept for the Community Interpreting, and evaluates them in terms of this new normal’s effects on the professionalization/professionalism process.
Thinking about “New Normal” in healthcare interpreting and community interpreting in terms of COVID-19 conditions